2019
DOI: 10.1209/0295-5075/125/30002
|View full text |Cite
|
Sign up to set email alerts
|

Singularity-free black holes in conformal gravity: New observational constraints

Abstract: We consider the family of singularity-free rotating black hole solutions in Einstein's conformal gravity found in Ref.[1] and we constrain the value of the conformal parameter L from the analysis of a 30 ks NuSTAR observation of the stellar-mass black hole in GS 1354-645 during its outburst in 2015. Our new constraint is much stronger than that found in previous work. Here we obtain L/M < 0.12 (99% confidence level, statistical uncertainty only).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…We have extended this model to RELXILL_NK, which can calculate the reflection spectrum for non-Kerr metrics [15,16]. The model has been applied to x-ray observations of several astrophysical BHs to place constraints on deviations away from the Kerr solution [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…We have extended this model to RELXILL_NK, which can calculate the reflection spectrum for non-Kerr metrics [15,16]. The model has been applied to x-ray observations of several astrophysical BHs to place constraints on deviations away from the Kerr solution [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The application of conformal invariance in alternative theories of gravitation has had a long history among relativists and has even been considered as a tool to solve the singularity issue in general relativity [118]. In this regard, joining conformal symmetry with general relativistic black hole spacetimes, research has shown that it is possible to obtain singularity-free black holes in conformal gravity that can be confined successfully within the mass and the radiation spectrum of the Schwarzschild and Kerr black holes [119][120][121].…”
Section: Discussionmentioning
confidence: 99%
“…[3,15], we presented the first version of the relativistic reflection model relxill_nk, which is an extension of the relxill package developed by Thomas Dauser and Javier Garcia [23,30,31]. As nkbb, the default version of relxill_nk employs the Johannsen metric with the possible non-vanishing deformation parameter α 13 [38], but modified versions of relxill_nk have been used to test black hole solutions in conformal gravity [80,82], in Kaluza-Klein models [84], in asymptotically safe quantum gravity [83], and in Einstein-Maxwell dilaton-axion gravity [69], as in all these theories we know the analytic expression of the metric of rotating black holes. relxill_nk has also been used for testing the Weak Equivalence Principle [58], while we have not used our model for testing the atomic physics in the strong gravitational fields of black holes.…”
Section: Continuum-fitting Methodsmentioning
confidence: 99%